Strategic Integration of Transfer Pricing Policies in Multinational Enterprises - Elien Basaria Sikettang; Ardin Doloksaribu; Klaudia Stefani Manik; Debora Maureen; Elda Sianturi; Melisa Febriani Siagian; Rodo Graecias Nainggolan; James Saragih (Golden Ratio of Data in Summary, 2026)
This study examines the strategic integration of transfer pricing policies within multinational enterprises by exploring their managerial, strategic, and international taxation dimensions. The study aims to explain how transfer pricing extends beyond an internal pricing mechanism to support management control, corporate strategy, operational efficiency, and regulatory compliance in an increasingly complex global business environment. A qualitative approach was employed using a semi-systematic literature review to synthesize multidisciplinary evidence from management accounting, international taxation, strategic management, and international business. The reviewed literature was analyzed through thematic analysis to identify the principal concepts, patterns, and relationships concerning transfer pricing policies. The findings indicate that effective transfer pricing policies function as strategic management instruments that facilitate organizational coordination, performance evaluation, resource allocation, tax compliance, and corporate governance. The review also demonstrates that inadequate strategic integration may increase interdivisional conflicts, distort managerial performance measurement, and expose multinational enterprises to greater tax adjustment and regulatory risks. Furthermore, recent international tax reforms, including the OECD Base Erosion and Profit Shifting (BEPS) initiative and the Global Minimum Tax, require multinational enterprises to balance tax efficiency with transparency, economic substance, and sustainable value creation. This study contributes to the literature by providing an integrated conceptual perspective that connects management accounting, international taxation, strategic management, and corporate governance in explaining the strategic role of transfer pricing within multinational enterprises.